PENGARUH KOMPOSISI ALAT BERAT PEKERJAAN TANAH TERHADAP BIAYA ALAT OPTIMUM - Sitti Safiatus Riskijah; Radhia Jatu Noviarsita Sakti; Agustin Dita Lestari (Prokons: Jurnal Teknik Sipil, 2022)
AbstractThe normalization and widening work volume of the Kali X is huge, it needs heavy equipment for its implementation. The type of usable heavy equipment varies, whilst the greater the capacity of the used equipmen, the more expensive the cost. Therefore, research is needed to observe the effect of heavy equipment composition on its optimal cost. The data needed are plan drawings, RKS, volume of work, equipment rental prices and wages, schedules and S curves. We determine the optimal tool costs using simplex method with the LINDO application and analyse the effect using linear regression analysis with SPSS. The obtained results of the effect analysis show that the composition of heavy equipment (expressed by total tool productivity) contributes a very strong and significant influence to the optimal cost of heavy equipment with R2 = 0.967 in clearing excavation work, R2 = 0.908 in ordinary excavation work, and R2 = 0.985 on embankment work. This shows that the composition of heavy equipment with lower productivity means the cost of using the tool is getting cheaper, so the results of optimizing the cost of using the tool are focused on the composition of tools with the lowerst productivity.Keywords: Excavation work, embankment work, combination of heavy equipment, optimal cost